CANVA SEBAGAI MEDIA PEMBELAJARAN IPA MATERI PERPINDAHAN KALOR DI SEKOLAH DASAR - Tiara Melinda; Erwin Rahayu Saputra (PGSD UNIKA SANTU PAULUS RUTENG, 2021)
Canva as a Science Learning Media to Heat Transfer Material in Elementary School. This article is formulated as the development of learning media in elementary schools, this is motivated by the lack of variety of learning media by utilizing current technological developments. This study uses a development research method with a descriptive approach based on the relevant literature. The development of this learning media is aimed at the subject of Natural Sciences (IPA), especially on the material of heat transfer. The purpose of developing this learning media is so that students learn according to their developmental stages, elementary school students are at the concrete operational stage. This stage is the third stage based on the stage of cognitive development according to Piaget. At this stage the child needs a concrete object or a habit of learning. Using Canva as a learning medium can make it easier for teachers in teaching and learning activities. Learning materials can be animated using the features available in Canva. Thus, students can learn with concrete objects in the form of animations in the science subjects of heat transfer material.